STRATEGI PEMASARAN INDUSTRI MADU PADA PT MADU PRAMUKA DI KABUPATEN BATANG - Eka Pratiwi; Sugiharti Mulya Handayani (Universitas Sebelas Maret, 2010)
This research purposes are to identify the external and internal factors that can be the strength, weakness, opportunity, and threat to find the strategic alternative and to determine the strategic priority applied in the marketing of honey industry in PT. Madu Pramuka, Batang Regency. The basic method of this research is a descriptive method. The types of data used in this research are primary and secondary data. The method of analyzing the data are the descriptive-qualitative, Matrix EFE, Matrix IFE, Matrix IE, Matrix SWOT, and Matrix QSP. The results of this research show that there are several strategic alternatives of the marketing found, such as: making a qualified hone, creating the best product of honey, keeping the original and purity of honey and also the various kinds of honey products to increase the consumers loyalty to the compeny; keeping the product continuity by making a good relationship with the suppliers; increasing the cooperation with the Research and Development Institute to develop the product of honey; increasing the sale based on the segment of the geographical market, the targeted market, and the channel of the short distribution; exploiting the higher technology to get the honey containing the low amount of water; increasing the sale promotion through the events organized by the local government; keeping on update the information about honey product by using the internet; making the honey product stand when there is an important event held, making leaflets and catalogues and introduction of the bee sting in the purposed market segment; increasing the scale volume by making a competitive price promotion for the purposed market segment; giving the best service to the consumers in order that they are always loyal and keep on trusting the product of honey; increasing the adequate supply of honey during the period of shortage before harvest; making the recording of the production and sale data in detail; determining the competitive price for increasing the sale, thus the fee can be lower. The applicable priority strategy are to make a qualified honey production, to create the best product of honey, to maintain the purity and original of honey, and to keep the various kinds of honey production for increasing the consumer’s loyalty toward company.